2014
DOI: 10.1179/1476830514y.0000000119
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperalgesic and antidepressive actions of (R)-(+)-limonene, α-phellandrene, and essential oil fromSchinus terebinthifoliusfruits in a neuropathic pain model

Abstract: Together, the results of the present work show that essential oil of S. terebinthifolius and compounds present in this oil, including (R)-(+)-limonene and α-phellandrene, exhibit antihyperalgesic effects against mechanical hyperalgesia, and are antidepressive, while only α-phellandrene inhibited cold hyperalgesia in SNI rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 27 publications
0
49
0
5
Order By: Relevance
“…It is used in many household cleaners, perfumes, and foods. Studies have shown characteristics including anti‐inflammatory, analgesic, antioxidant, antidepressant and immunostimulating benefit, anti‐cancer against skin cancer, breast cancer, prostate cancer, other advanced solid tumors such as recurrent glioblastoma, anti‐bacterial, anti‐fungal, and antimalarial, and acts as insect repellent . Limonene is active against acne, dermatophytes, and GERD .…”
Section: Terpenes (Terpenoids)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is used in many household cleaners, perfumes, and foods. Studies have shown characteristics including anti‐inflammatory, analgesic, antioxidant, antidepressant and immunostimulating benefit, anti‐cancer against skin cancer, breast cancer, prostate cancer, other advanced solid tumors such as recurrent glioblastoma, anti‐bacterial, anti‐fungal, and antimalarial, and acts as insect repellent . Limonene is active against acne, dermatophytes, and GERD .…”
Section: Terpenes (Terpenoids)mentioning
confidence: 99%
“…Phellandrene is found in eucalyptus, water fennel, lavender, grand fir, and found in several herbs and spices including cinnamon, dill garlic, ginger and parsley. It has analgesic and anti‐depressive effects …”
Section: Terpenes (Terpenoids)mentioning
confidence: 99%
“…Ainda há uma possível ação antidepressiva (PICCINELLI et al, 2015), efeito hepatoprotetor (ABDOU et al, 2015) e fotoprotetor (BULLA et al, 2015).…”
Section: Usos Variados Da Aroeiraunclassified
“…clinopodioides (2.0%) [184] Inhibition of P-glycoprotein-mediated transport of different substances [213] Suppression of CNS in mice [214,215] Some topical anti-inflammatory activity in carrageenan-induced paw edema in rats [216] Antioxidant activity in various free radical scavenging tests [217,218] Antifungal activity tested against some food spoilage yeasts [219] Larvicidal activity against mosquitoes Aedes aegypti and A. albopictus [206] Antiviral activity against herpes simplex virus type 1 in vitro [220] Review on some effects on cardiovascular system [221] Trypanocidal activity against Trypanosoma evansi [222] Z. tenuior (0.48%) [94,179] α-Phellandrene (35) Z. clinopodioides (0.3%) [184] Insecticidal activity against various species of insects [192,193]; larvicidal activity against various mosquito species [205,206] Antinociceptive activity assessed in various chemical-induced nociception models in rodents [207,208] Antidepressant activity in rats [208] Induction of autophagy in human liver tumour cells [209]; induction of necrosis [210]; induction of apoptosis in mice leukaemia WEHI-3 cells in vitro [211]; promotion of the immune response by increasing the level of T-cells, monocytes and macrophages in BALB/c mice in vivo [212] α-Terpinene (36)…”
Section: α-Thujene (34)mentioning
confidence: 99%
“…rigida (0.1%) [21] Z. clinopodioides subsp. bungeana [201] Z. tenuior (0.48%) [94,179] Insecticidal activity against various species of insects [192,193]; larvicidal activity against various mosquito species [205,206] Antinociceptive activity assessed in various chemical-induced nociception models in rodents [207,208] Antidepressant activity in rats [208] Induction of autophagy in human liver tumour cells [209]; induction of necrosis [210]; induction of apoptosis in mice leukaemia WEHI-3 cells in vitro [211]; promotion of the immune response by increasing the level of T-cells, monocytes and macrophages in BALB/c mice in vivo [212] Molecules 2016, 21, 826 14 of 53…”
Section: α-Thujene (34)mentioning
confidence: 99%